Assessing the Performance of Analytical Procedures: A Best Case Scenario. - Wheeler, Stephen; Pany, Kurt (The Accounting Review, 1990)
Evaluates the extent to which analytical procedures used by auditors provide correct signals as to the existence of material misstatements under `best case' circumstances. Expectation models; Materiality definitions for error seedlings; Accounting error types.